Small-scale fisheries and sustainable development: Key findings from the IHH report - Bevitt, Kate Melinda; Franz, Nicole; McCormack, Stacey (Food and Agriculture Organization of the United Nations, 2022)
This brief presents the main results from the Illuminating Hidden Harvests (IHH) report, providing new, clearer insights to support the implementation of the Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries in the Context of Food Security and Poverty Eradication (SSF Guidelines) and progress toward the Sustainable Development Goals (SDGs).